A PLC-based Hybrid Fuzzy PID Controller for PWM-driven Variable Speed Drive - ARROFIQ, MUHAMMAD (2010)
In adjustable-speed drive applications, the range of speed and torque achievable is very important. A power electronic converter is needed as an interface between the input AC power and the drive. A controller is needed to make the motor (drive), through the power electronics converter meets the drive requirements. The widely used conventional control that is based on mathematical model of the controlled system is very complex and not easy to be determined since it requires explicit knowledge of the motor and load dynamics. This thesis proposed a design and implementation of a PLC-based hybrid controller from a basic PLC to a PWM-driven variable-voltage variable-frequency (VVVF) speed control of an induction motor and the analysis, evaluation and improvement of the control strategies. A simulation model in MA TLAB/Simulink is developed using system identification technique to perform verification of the PLCbased intelligent controller of the PWM-driven VVVF algorithm. To provide stability in response to sudden changes in reference speed and/or load torque, a switching type controller consisting of two control modes are devised: a PID-type fuzzy controller consisting of a PI-type and a PD-type fuzzy controller, and a conventional PID. The proposed scenario is implementing a strategy when the actual value is closed to setpoint. At the early phase of the control action, the control task is handled by the PIDtype fuzzy controller. At a later phase when the absolute of error is less than a threshold value, the input of integrator at the output side is no longer given by fuzzy action but fed by the incremental PID action. In term of control action, this is an enhanced proportional and derivative action when the actual value is closed to reference. Detailed evaluations of the controller's performance based-on a predefined performance indices under several conditions are presented. The findings demonstrate the ability of the control approach to provide a viable control solution in response to the different operating conditions and requirements.